Iron deficiency in the elderly population, revisited in the hepcidin era - Busti, Fabiana; Campostrini, Natascia; Martinelli, Nicola; Girelli, Domenico (Frontiers in Pharmacology, 2014)
Iron deficiency (ID) is relatively common among the elderly population, contributing substantially to the high prevalence of anemia observed in the last decades of life, which in turn has important implications both on quality of life and on survival. In elderly subjects, ID is often multifactorial, i.e., due to multiple concurring causes, including inadequate dietary intake or absorption, occult bleeding, medications. Moreover, because of the typical multimorbidity of aged people, other conditions leading to anemia frequently coexist and make diagnosis of ID particularly challenging. Treatment of ID is also problematic in elderly, since response to oral iron is often slow, with a substantial fraction of patients showing refractoriness and requiring cumbersome intravenous administration. In the last decade, the discovery of the iron regulatory hormone hepcidin has revolutionized our understanding of iron pathophysiology. In this review, we revisit ID among elderly people in the light of the impressive recent advances on knowledge of iron regulation, and discuss how hepcidin may help in diagnosis and treatment of this common clinical condition.